Xyela kamtshatica Gussakovskij 1935 - Blank, Stephan M.; Shinohara, Akihiko; Altenhofer, Ewald (Zenodo, 2013)
Xyela kamtshatica Gussakovskij, 1935 JAPAN: Honshu, Ishikawa Pref., Mount Haku [136.77°E 36.15°N], 22.7.1962, 1♀ ZMUM [“ X. ? kamtshatica ” of Rasnitsyn 1965, here only tentatively identified due to bad preservation]; same data, 22.7.1968, 2♀ 5♂, NSMT; same data, 2000–2700 m alt., 15.7.1981, leg. I. Togashi, 4♀ 4♂, NSMT; Ishikawa Pref., Mount Haku, Murodaira, 15.7.1981, leg. I. Togashi, 3♀ 1♂, NSMT; Honshu, Ishikawa Pref., Mount Haku, Ohana Matsubara, 22.7.1962, 1♂, NSMT. RUSSIA: Kamchatskaya Oblast, sel [= village] Klyuchevskoe na r. [= na reka, on river] Kamchatk’ [= Kamchatka, Klyuchi] [160.85°E 56.30°N], 6.6.1909, leg. A. Derzhavin, 1♀, ZIN [holotype, Gussakovskij 1935]. : Published as part of Blank, Stephan M., Shinohara, Akihiko & Altenhofer, Ewald, 2013, The Eurasian species of Xyela (Hymenoptera, Xyelidae): taxonomy, host plants and distribution , pp. 1-106 in Zootaxa 3629 (1) on page 101, DOI: 10.11646/zootaxa.3629.1.1, http://zenodo.org/record/5261330